Proof without words: four circles - Plaza, Ángel (Teaching Mathematics and Computer Science, 2005)
Theorem. Let O, P and Q be three points on a line, with P lying between O and Q. Semicircles are drawn on the same side of the line with diameters OP, PQ and OQ. An arbelos is the figure bounded by these three semicircles. Draw the perpendicular…